Improving antifouling ability and hemocompatibility of poly(vinylidene fluoride) membranes by polydopamine-mediated ATRP. Issue 39 (4th September 2015) - Jiang, Jinhong; Zhang, Peibin; Zhu, Liping; Zhu, Baoku; Xu, Youyi
Abstract : A versatile strategy for the preparation of polymer membranes with remarkably improved antifouling properties and hemocompatibility is developed through a simple blending process and secondary treatments. Abstract : The present work aims to improve the antifouling properties and hemocompatibility of poly(vinylidene fluoride) (PVDF) membranes by polydopamine-mediated atom transfer radical polymerization (ATRP). Polydopamine (PDA) was first prepared by the oxidation and self-polymerization in basic aqueous solution. The obtained PDA was used as an additive in the preparation of PVDF membranes via non-solvent induced phase separation (NIPS). Then poly(sulfobetaine methacrylate) (PSBMA), a commonly used zwitterionic polymer, was successfully grafted from the entrapped PDA in membranes through ATRP. The changes in surface morphologies of the PVDF membranes before and after modification were observed by scanning electronic microscopy (SEM) and atomic force microscopy (AFM). Data of water contact angle measurements indicated that the surface hydrophilicity of the modified membranes was remarkably improved compared with that of the pure PVDF membrane. Results of filtration tests revealed that the water permeability and antifouling properties of the PVDF membranes were both increased after modification. Moreover, the hemocompatibility of the modified PVDF membrane was greatly improved due to the incorporation of zwitterionic brushes as demonstrated by in vitro platelet adhesion. Owing to the chemical reactivity of polydopamine as well as its strong interactions with a wide spectrum of solid substrates, this strategy can be extended to other materials and allows the development of novel functional membranes through such a blending process and secondary treatments.